Pengaruh Teknologi Informasi Komunikasi Dan Budaya Literasi Di Masa Pandemi Covid-19 - Yayu Siti Wahyuni; Leli Patimah, Leli Patimah (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2022)
Abstract Education is an effort carried out with the aim of making one's life better, more useful, and as a means to express all the potential that exists within oneself in order to become a better person than before. The presence of COVID-19 has had a significant impact in various sectors, especially in the education sector. Many changes have occurred due to the presence of this pandemic. Today's society is required to be literate in all things, especially in terms of technology. Distance learning (PJJ), which has been implemented since the presence of the COVID-19 pandemic, presents new habits that have never happened before. The ability to be technologically literate is a basic ability as well as a very important ability that must be possessed by anyone involved in the world of education. At this time, technology has become a bridge between teachers and students so that learning can continue. Information and communication technology literacy is also present as a solution that will help streamline the distance learning process because information and communication technology literacy includes all knowledge and skills in utilizing technology, starting from knowing the device, how to operate the device, to using it.